Tag-single nucleotide polymorphism-based human leukocyte antigen genotyping in celiac disease patients from northeastern Italy. - Vatta, Serena; Fabris, Annalisa; Segat, Ludovica; Not, Tarcisio; Crovella, Sergio (Hum Immunol, 2011)
We genotyped celiac disease (CD)-associated haplotypes DQ2.5, DQ8, DQ2.2, and DQ7 in 1005 CD patients from North Eastern Italy using a Tag-single nucleotide polymorphism (SNPs) approach and real time PCR platform, checking the accuracy and reliability of the method and comparing it to traditional PCR-SSP. Only 14 of 2010 chromosomes analyzed (0.7%) showed discrepancies between the Tag-SNPs real-time polymerase chain reaction (PCR) method and the PCR-single-strand polymorphism (SSP) technique, indicating a high sensitivity and specificity (ranging from 0.987 to 1 and from 0.998 to 0.999, respectively) for tagging with respect to corresponding human leukocyte antigen (HLA) alleles identified by PCR-SSP. Moreover, the overall cost of the Tag-SNPs HLA typing method was low (3 to 4 €/sample instead of 35 to 70 €/sample with commercial kits), making it suitable for mass screenings. Hence, we believe that the Tag-SNPs HLA typing could be used to complement or replace classic HLA typing in at high-risk groups, for research purposes and eventually in population screening programs.
Keywords: Adolescent; Adult; Aged; Celiac Disease; Child; Child, Preschool; Female; Humans; Infant; Italy; Male; Mass Screening; Middle Aged; Polymerase Chain Reaction; Polymorphism, Single Nucleotide; Reproducibility of Results; Reverse Transcriptase Polymerase Chain Reaction; Sensitivity and Specificity